Figure 1 from: Cripps CL, Eberhardt U, Schütz N, Beker HJ, Evenson VS, Horak E (2019) The genus Hebeloma in the Rocky Mountain Alpine Zone. MycoKeys 46: 1-54. https://doi.org/10.3897/mycokeys.46.32823 - Cripps, Cathy L.; Eberhardt, Ursula; Schütz, Nicole; Beker, Henry J.; Evenson, Vera S.; Horak, Egon (Zenodo, 2019)
Figure 1 Distribution of Rocky Mountain alpine collections of Hebeloma. The map was generated with QGIS version 2.2.0 using WGS84 (EPDG: 4326; QGIS Development Team 2018). Shapefiles were provided by the Database of Global Administrative Areas (GADM, https://gadm.org/), accessed April 2018.